2005
DOI: 10.1037/0096-1523.31.6.1416
|View full text |Cite
|
Sign up to set email alerts
|

Task Demands Control Acquisition and Storage of Visual Information.

Abstract: Attention and working memory limitations set strict limits on visual representations, yet researchers have little appreciation of how these limits constrain the acquisition of information in ongoing visually guided behavior. Subjects performed a brick sorting task in a virtual environment. A change was made to 1 of the features of the brick being held on about 10% of trials. Rates of change detection for feature changes were generally low and depended on the pick-up and put-down relevance of the feature to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
91
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 92 publications
15
91
1
1
Order By: Relevance
“…Increasing VWM load may also have reduced the probability that VWM would be used during online perception. Indeed, during visually guided motor tasks-such as picking up a colored block and placing it at a designated locationparticipants usually acquire one relevant feature at a time, rather than storing all features of an object simultaneously (Ballard et al, 1995;Droll et al, 2005;Hayhoe & Ballard, 2005). These findings suggest that although it is possible to store a few objects in VWM under ideal conditions, the interaction between VWM and online perception might be most obvious when VWM is not fully loaded.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Increasing VWM load may also have reduced the probability that VWM would be used during online perception. Indeed, during visually guided motor tasks-such as picking up a colored block and placing it at a designated locationparticipants usually acquire one relevant feature at a time, rather than storing all features of an object simultaneously (Ballard et al, 1995;Droll et al, 2005;Hayhoe & Ballard, 2005). These findings suggest that although it is possible to store a few objects in VWM under ideal conditions, the interaction between VWM and online perception might be most obvious when VWM is not fully loaded.…”
Section: Resultsmentioning
confidence: 69%
“…For example, Hayhoe and colleagues (Ballard, Hayhoe, & Pelz, 1995;Droll, Hayhoe, Triesch, & Sullivan, 2005;Hayhoe & Ballard, 2005) found that during visually guided motor tasks-such as d picking up a blue block and placing it at a designated location-participants usually do not fill up their VWM f capacity. Instead, they prefer to keep a single piece of information in VWM at once and look back at a display again when more information is needed.…”
mentioning
confidence: 99%
“…3 just points out a standard way of purposefully interacting with the environment, but there are many others. Subjects manipulating blocks in another virtual world code the color of a block in a single fixation at the beginning of a trial and then are apt to miss catch trial color changes to the block, even when cued to look for changes (Droll et al, 2005). Subjects searching for an object in a large image using a remembered preview of the image have very different scanning patterns than subjects who are just given a small image icon containing the target (Rao et al, 2002).…”
Section: Evidence For Routinesmentioning
confidence: 99%
“…The partitioning of the two lines of research in practice partly derived from and partly fostered a bipartite view of sensorimotor processing in the brain -that a sensory/perceptual system creates a general purpose representation of the world which serves as the input to the motor systems (and other cognitive systems) that generate action/behavior as an output. Recent results from research on vision in natural tasks have seriously challenged this view, suggesting that the visual system does not generate a generalpurpose representation of the world, but rather extracts information relevant to the task at hand (Droll et al, 2005;Land and Hayhoe, 2001). At the same time, researchers in motor control have developed an increasing understanding of how sensory limitations and sensory uncertainty can shape the motor strategies that humans employ to perform tasks.…”
Section: Introductionmentioning
confidence: 99%